Prototype Mentoring Pengembangan Karakter Mahasiswa Dengan Metode Profile Matching - Mustakim Mustakim; Imam Suharjo (Jurnal Tika, 2023)
Character is an important aspect that students must have to face challenges in the global era. However, each student has a different character, not all have the same potential due to different interests, desires, and abilities. Therefore, a program is needed that can help students develop their character according to their potential and interests. One program that can be used is mentoring, which is a guidance and development process carried out by Academic Supervising Lecturers to their students. Mentoring can improve academic quality, skills, and student character through intensive, personal, and ongoing interaction. This research focuses on the development of student character through mentoring carried out by Academic Supervising Lecturers to their students. This research was conducted by having students fill in data to carry out self-evaluation with parameters of 16 skills that must be mastered in the 21st century based on the World Economic Forum Report in 2015. Each skill chooses the lowest value of 1 and the highest of 7. The evaluation value can be known by the students themselves with the output of three skills with the highest potential and 3 lowest that need to be developed. The profile matching method is used to calculate the total value that will be used for ranking. This highest value can be seen by each academic supervising lecturer for their students. The result of this research is a Prototype that can help students develop their character according to their potential and interests. This prototype can also improve the quality of education in colleges by creating a harmonious, effective, and productive mentoring relationship.